THE POTENCIAL TOLERANCE OF PROBIOTIC DADIAH TO ZINC “NOVEL OF OBESITY THERAPY” - Siana, Yusti; Faridah Mohd Said; Devi Nallappan; Rinita Amelia; Yudha Endra Pratama (Nusantara Hasana Journal, 2026)
Dadiah is included in functional food because it contains lactic acid bacteria (LAB) which have the potential to be probiotics. The combination of foods containing bacteria with other compounds must be treated so that they do not inhibit or kill lactic acid bacteria. Zinc as one of the micronutrients that is important for the body and is also an antimicrobial but has benefits for obese people. Giving LAB with zinc should provide support to each other without reducing the impact of any of the materials used. This study aims to determine the tolerance of probiotic potential lactic acid bacteria to zinc so that zinc resistant LAB isolate is obtained to be applied to obese patients. To determine the correlation and relationship of zinc and LAB, observations were made on the microscopic and macroscopic characteristics of LAB from Bukitinggi drugs such as fermentation type, catalase test, gram staining and zinc resistance using the welling method and total colony. The results obtained in the study obtained 5 isolates from Bukittinggi curdiah, all isolates including homofermetative fermentation types, negative catalase tests and including Gram Positive results from gram staining. LAB resistance to zinc using the well method did not obtain clearzone for all isolates and LAB resistance to zinc obtained viability below 20% for all isolates. In the research that has been done, it was found that LAB isolated from Bukittinggi drug has characteristics that have potential as probiotics and are also resistant to zinc so that the combination of LAB and zinc for obese patients can be carried out to the next stage.